2003
DOI: 10.1051/0004-6361:20031214
|View full text |Cite
|
Sign up to set email alerts
|

3D mapping of the dense interstellar gas around the Local Bubble

Abstract: Abstract. We present intermediate results from a long-term program of mapping the neutral absorption characteristics of the local interstellar medium, motivated by the availability of accurate and consistent parallaxes from the Hipparcos satellite. Equivalent widths of the interstellar NaI D-line doublet at 5890 Å are presented for the lines-of-sight towards some 311 new target stars lying within ∼350 pc of the Sun. Using these data, together with NaI absorption measurements towards a further ∼240 nearby targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
463
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 367 publications
(488 citation statements)
references
References 59 publications
23
463
0
2
Order By: Relevance
“…This is a strong indication that the distribution of material around the Sun is far from uniform and that interfaces are not seen in all directions. We already know from earlier studies of the LISM, culminating in the work of Lallement et al (2003), that boundary of the Local Bubble is not equidistant from the Sun in all directions. Nor is it a simple shape.…”
Section: O VI Column and Volume Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a strong indication that the distribution of material around the Sun is far from uniform and that interfaces are not seen in all directions. We already know from earlier studies of the LISM, culminating in the work of Lallement et al (2003), that boundary of the Local Bubble is not equidistant from the Sun in all directions. Nor is it a simple shape.…”
Section: O VI Column and Volume Densitiesmentioning
confidence: 99%
“…This is now provided by our interpretation of Figure 8. Figure 8 indicates the location of a selection of the stars listed in Table 3 and shows a number of slices through the local ISM based on the 3-D spatial distribution of neutral gas presented by Lallement et al (2003), but updated by Welsh et al (2010) with more recent information. On each of the projections shown, we have plotted the positions of detections of interstellar O VI along with the most sensitive non-detections.…”
Section: O VI Column and Volume Densitiesmentioning
confidence: 99%
“…These different components of the hydrogen column density are estimated by different measurement Fig. 2 The limits of using the Ferlet et al (1985) formula The sodium column density as derived from the density data by Lallement et al (2003) is shown in galactic cartesian coordinates at z=0; x is towards the galactic center which is at the right, y towards l=90 • is pointing up. The image spans 500 pc times 500 pc.…”
Section: The Inhomogeneously Distributed Ismmentioning
confidence: 99%
“…Current interstellar absorption treatment depends on chosen abundances and scattering cross-sections of the elements as well as on the 3D distribution of the interstellar medium. After a discussion of these factors we use the comprehensive 3D measurements of the Local Bubble by Lallement et al (2003) to construct two simple models of the 3D distribution of the hydrogen column density. We test these models by using a set of soft X-ray sources with known distances.…”
mentioning
confidence: 99%
“…The local ISM The Sun lies inside the Local Bubble, a large ionised gas bubble that extends outwards from the Sun to a neutral hydrogen column density log N (H I) ≈ 19.2 (cm −2 units), corresponding to a geometrical size of 100-200 pc depending on the direction from the Sun. The Local Bubble's morphology has been identified by Na I absorption, which is formed in the cold gas than surrounds the Local Bubble and determines its shape (Lallement et al, 2003). The Local Bubble is thought to be an H II region formed by the explosions of supernovae and the strong winds of young hot stars in the Lower Centaurus Crux subgroup of the Scorpio-Centaurus Association (Maíz-Apellániz, 2001;Berghöfer and Breitschwerdt, 2002).…”
Section: Halo-disk Interaction In the Milky Waymentioning
confidence: 99%